O Boulevard Shopping Center e a formação de uma Nova Centralidade em Campina Grande - PB - Batista, Péricles Alves (2011)
This paper refers to research in the area surrounding the Boulevard Mall in Campina Grande, in order to deal with these changes and restructuring in the urban space of Campina Grande - PB, in the period 1999 to 2011. The research reveals the changes which have occurred in Campina Grande in the last decade, due mainly (but not exclusively), to the installation of the Boulevard Mall. Thus, there is a real process in this period of urban restructuring in the city, represented by the decentralization of some commercial activities and services in the traditional center, driven by the expansion of the city in East direction along with the direction of that mall s place. In order to verify this fact, a survey of urban land use in Otacílio Nepomuceno Street and Severino Cabral Avenue was conducted, in order to count the number of shops and services, land and homes. In addition to analyzing these two access roads to the mall, observations of the streets lying across these pathways were also made. We made the documentary research through analyzing newspapers, in order to gather information for the period prior to the construction of the mall, as well as in classified real estate sales in the years after the inauguration of the project, to see the process of valuation of urban land in this area.In addition, interviews with some former residents of Catolé neighborhood and with employees who work in dealerships around the Boulevard Mall were carried out. The research reveals the formation of a new centrality in Campina Grande, in the area located in the neighborhoods of Mirante, José Pinheiro and especially Catolé neighborhood. This process has triggered several changes in space. The Catolé neighborhood, particularly, used to have exclusively residential profile, but has undergone intense restatements in the last decade and has become a major area provider of services, including becoming the unifying area of flows originated not only from other neighborhoods in the city, as well as from other municipalities in the state, and neighboring states.